The Genus Yaberinella in Costa Rica: Record and Implications - Chesnel, Valentin (2021)
The genus Yaberinella is systematically described for the first time in Costa Rica. Measurements of features such as the mean proloculus diameter and the count and mean length (in axial sections) of whorls are used to help determining affiliation of two distinct species. Being relatively rare in the geological record and apparently restricted to the Caribbean region – with a controverted apparition in western Oman –, its presence in Pacific side´s deposits of Costa Rica is worth to mention. Besides, the presence of Yaberinella hottingeri together with Y. panamensis suggests an extension of the first species time slice.